Screening of Antimicrobial Activity of Essential Oil of Thymus Vulgarison Some Pathogens - Raho G, Bachir; Z, Benattouche; A, Bevilacqua; MR, Corbo; M, Sinigaglia; S, Pignatiello (Journal of Diseases, 2014)
The inhibitory effects of Thymus vulgaris essential oils were screened against Coliform spp, Pseudomonas spp, Saccharomyces cerevisiae (EC1118), Zygosaccharomyces bailii (DSM 70492) and Lactobacillus plantarum (DSM2601) by agar well diffusion method. Results obtained in thisstudy revealed that the essential oils of Thymus vulgaris posses a weak antibacterial effect against the tested microorganisms with small inhibition zones ranged between 0 and 4 mm. This activity was dose independent. Z. baillii was more susceptible to T. vulgaris essential oils, while Coliform spp was more resistant comparing to other tested microorganisms.